UPAYA PENYELESAIAN SENGKETA INDONESIA BRAZIL TERKAIT IMPOR PAHA AYAM DI WTO PERIODE 2014-2016 - Hartika, - (2018)
This study discusses Brazil's lawsuit against Indonesia in the settlement of import dispute of chicken thighs period 2014 - 2016. The existence of a dispute caused by Indonesia to close the export of Brazilian chicken thighs that eventually made Brazil bring the issue into the realm of WTO. This research raises the research question "how is the Brazilian dispute settlement process related to the import of chicken thighs? "To answer that question the author uses a number of theories and concepts of international trade theory, the theory of international organizations, the concept of the WTO and the concept of dispute resolution WTO. This research method uses descriptive qualitative research method, which emphasizes on the use of primary data derived from interviews and other supporting data to describe and provide an understanding of the problems that occur. This study was conducted to find out the trade between Indonesia and Brazil. In addition, this study aims to understand the Brazilian dispute settlement process in the WTO and Indonesia's response in response to the Brazilian allegations, as well as to see how the WTO role in solving this problem